Massive Hip Heterotopic Ossification in a Polytrauma Patient: A Case Report - Reza Zandi; Shahin Talebi; Farnam Behroo; Saeed Nodehi; Akbar Ehsani (Journal of Orthopedic and Spine Trauma)
Background: Heterotopic ossification (HO) around the hip joint is correlated with a dramatic reduction in hip range of motion (ROM) and quality of life (QOL). Case Report: We report on a 45-year-old man with a massive right hip HO with intensive reduction in his right hip ROM. He underwent surgical resection via Smith-Petersen approach by an experienced hip surgeon, as well as a vascular surgeon. Neurovascular bundle was explored and protected. The mass was excised as much as possible. The ROM increased instantly to near full. After surgery, we used indomethacin in order to hinder the HO relapse. Conclusion: The surgical resection of hip HO is a feasible treatment option; however, it is challenging.